Adaptation and feasibility of a multimodal mindfulness-based intervention to promote sexual health in cancer survivorship. Issue 10 (24th June 2021) - Gorman, Jessica R; Drizin, Julia H; Al-Ghadban, Fatima A; Rendle, Katharine A
Abstract: Sexual health concerns after cancer are common and distressing, and mindfulness-based interventions (MBIs) are effective in supporting women experiencing these concerns. The goals of this study were to: (i) systematically adapt and document modifications to a mindfulness-based sexual health intervention for cancer survivors in a community setting and (ii) assess feasibility, appropriateness, and acceptability, and to identify strategies to increase reach for future implementation and dissemination. Following the ADAPT-ITT model, we first conducted key informant interviews with 10 female cancer survivors and four healthcare providers to obtain feedback on perceived need and feasibility of the intervention approach, and preferences for content, structure, and delivery format. This feedback informed initial intervention adaptations, which we then pretested with five female cancer survivors. We tracked and coded intervention adaptations. Key informant cancer survivors and providers confirmed the lack of sexual health services, acceptability of a sexual health MBI, and identified initial adaptations including modifying the intervention for delivery in a community, rather than clinical, setting. Pretest participants (aged 48–57) were survivors of breast ( n = 4) and cervical ( n = 1) cancer. All participants completed the intervention attending an average of 7.2 of 8 weekly sessions. Qualitative and quantitative results suggest the intervention was feasible, appropriate and acceptable. Engaging stakeholders in the adaptation process is essential for creating a feasible, appropriate, and acceptable intervention. Tracking intervention modifications contributes to our overall understanding of how MBIs can be adapted for new populations and contexts.